Mutual Analysis of Kutadgu Bilig and Siyasatnama in Terms of Work Ethics and Professions - Azizova, Elnura (Scholarya Demo Journal of Ruby, 2020)
This study examines two masterpieces of the Turkish cultural heritage belonging to the 11th century, Kutadgu Bilig by Yusuf Balasaguni, the Karahanian statesman and Siyasatnama the famous work by Nizam al-Muluk, the eminent vizier of the Great Seljuk period, in terms of work ethics and professions. Kutadgu Bilig which is translated as “Knowledge of Happiness”, beyond being just a book of ethics recommending happiness of two worlds to officials, especially the rulers, offers a holistic perspective by indicating the knowledge and virtues required in organizing ideal personal and community life as well as mutual relations. Beyond solely giving information about formation and functions of the state institutions of the Great Seljuks and their strengths and weaknesses, Siyasatnama provides valuable information about the work activity and working ethics of various segments of the society to fulfill the state and religious affairs with caution. In both works, there is extensive information about various professions in society, as well as government officials. Applying the comparative analysis method, the view of society to work ethics will be examined within the context of these two works written in different geographies of Turkish political administration in the same century. The research aims to identify the attitudes towards work activity and professions, as well as the source of these attitudes in Kutadgu Bilig and Siyasatnama. On the one hand, the cultural structure of the period will be clarified in both Turkish societies where the works were written, on the other hand, it will be evaluated in terms of the “ilm al-kasb” (knowledge of earning) in the history of Islamic economics.